Impact of long-term testosterone treatment on plasma levels of free TFPI and TF-induced thrombin generation ex vivo in elderly men with low testosterone levels - Agledahl, Ingvild; Brodin, Ellen; Svartberg, Johan; Hansen, John-Bjarne (Thrombosis and Haemostasis, 2009)
Men have a higher incidence of cardiovascular disease (CVD) than women of similar age, and it has been suggested that testosterone may influence the development of CVD. Recently, we demonstrated that elderly men with low testosterone levels had lower plasma levels of free tissue factor pathway inhibitor (TFPI) Ag associated with shortened tissue factor (TF)-induced coagulation initiation in a population based case-control study. Our hypothesis was that one year of testosterone treatment to physiological levels in elderly men would increase the levels of free TFPI Ag in plasma and have a favorable effect on TF-induced coagulation. Twenty-six men with low testosterone levels (≤11.0 nM) were randomly assigned to treatment with intramuscular testosterone depot injections (testosterone undecanoate 1,000 mg) or placebo in a double-blinded study. Each participant received a total of five injections, at baseline, 6, 16, 28 and 40 weeks, and TF-induced thrombin generation ex vivo and plasma free TFPI Ag were measured after one year. At the end of the study total and free testosterone levels were significantly higher in the testosterone treated group (14.9 ± 4.5 nM vs. 8.1 ± 2.4 nM; p<0.001, and 363.3 ± 106.6 pM vs. 187.3 ± 63.2 pM; p<0.001, respectively). Testosterone treatment for one year did neither cause significant changes in TF-induced thrombin generation ex vivo nor changes in plasma levels of free TFPI Ag. In conclusion, normalising testosterone levels by testosterone treatment for 12 months in elderly men did not affect TF-induced coagulation or plasma TFPI levels. The potential antithrombotic role of testosterone therapy remains to be elucidated.
Keywords: Men; testosterone; TFPI; thrombin generation